Brain Herniation in Neurofibromatosis with Dysplasia of Occipital Bone and Posterior Skull Base - Vithal Rangarajan; Amit Mahore; Manoj Patil; Prashant Sathe; Amol Kaswa; Sandeep Gore; Pralhad Dharurkar; Juhi Kawale (Case Reports in Neurological Medicine)
A 22-year-old female, a known case of neurofibromatosis 1 (NF1), presented with a congenital swelling in the left occipital region. She had developed recent onset dysphagia and localized occipital headache. Neuroradiology revealed a left occipital meningoencephalocele and a left parapharyngeal meningocele. This was associated with ventriculomegaly. She was advised on cranioplasty along with duraplasty which she denied. She agreed to a lumbar-peritoneal shunt. She described a dramatic improvement in her symptoms following the lumbar-peritoneal shunt. Occipital dysplasias, though uncommon, have been reported in the literature. We review this case and its management and discuss relevant literature on occipital dysplasias in NF1.